Dork Diaries : tales from a NOT-SO-Fabulous Life - Russell, Rachel Renée, ....- (New York : Aladdin, 2009)
Meet loveable, goofy Nikki Maxwell in this first installment of the mega bestselling Dork Diaries series!
Keywords: Diaries; Engels; Graphic Novels; Secundair onderwijs